Raw red onion intake and insulin resistance markers in overweight or obese patients with polycystic ovary syndrome: a randomized controlled-clinical trial - Ebrahimi-Mameghani, Mehranghiz; Saghafi-Asl, Maryam; Niafar, Mitra; Asghari-Jafarabadi, Mohammad; Mesgari-Abbasi, Mehran (Progress in Nutrition, 2018)
Background: Insulin resistance (IR) plays a pivotal role in the development of polycystic ovary syndrome (PCOS). Though hypoglycemic and hypolipidemic effects of onion have been suggested in type 2 diabetes mellitus, still, lack of data exist to investigate its hypoglycemic effect in PCOS. Objective: to assess the effects of raw red onion consumption on IR markers in PCOS. Methods: In this randomized controlled-clinical trial, 53 overweight or obese non-diabetic patients with PCOS were randomly allocated to either group of high-onion (HO; raw red onions: 2×40-50 g/day for overweight and 2×50-60 g/day for obese patients) or low-onion (LO; raw red onions: 2×10-15 g/day) for an 8 weeks. Fasting and 2-hour blood sugar, insulin, total testosterone, and progesterone, as well as homeostasis model of insulin resistance (HOMA-IR) and quantitative insulin sensitivity check index (QUICKI) were measured at baseline and after treatment. IR was defined as HOMA-IR≥3.8 in PCOS. Anthropometric indices and dietary intake were also evaluated. Results: After 8 weeks, no differences were observed in the IR markers including HOMA-IR neither within nor between the HO (from 3.53±1.22 to 4.08±1.70; P=0.090) and LO groups (from 3.58±1.75 to 3.32±1.36; P=0.338). Anthropometric and dietary parameters did not differ between the two groups (P>0.050). However, a non-significant increase was observed in the rate of menses occurrence in HO (17%) compared to LO group (6%) after 8 weeks. Conclusions: Although raw red onion intake could not significantly improve IR markers in non-diabetic patients with PCOS, it could increase the chance of menses occurrence. Further investigations are warranted to determine the effects of onion in these patients.